A review of Internet-based approaches for health promotion programs related to the COVID-19 pandemic and wellness education - Carissa Wityadarda; Gusti Ayu Sinta Deasy Andani; Rina Rostarina (Journal of Community Empowerment for Health, 2021)
COVID-19 pandemic continues to have significant impacts in various sectors of society worldwide, including Indonesia. One major impact of COVID-19 occurs in the health information sector especially with social distancing regulations that inhibit people to access health care providers. This has led to several other problems such as behavior alteration involving unhealthy lifestyles and misleading information. Due to the limitations of social interaction, health care providers have proposed various methods to provide health promotions related to COVID-19 and wellness education that are accessible by the whole society with or without Internet access. This study aimed to review the current strategies of health information systems to increase knowledge about COVID-19 and overall wellness by the implementation of Internet-based programs. This review is based on a secondary study conducted with online search engines. Some previous studies showed that online training has improved knowledge significantly. Other research also described how the success of a community education program depends on adequate motivation and access to proper information. Three main factors that cause the failure of community education are lack of self-efficacy, lack of information, and distraction without proper supervision. Lack of information is due to the difficulty to gain Internet access in some areas and for some populations. In conclusion, Internet-based approaches can be implemented for health promotion programs related to COVID-19 and wellness due to the massive growth of Internet use in Indonesia.